Use of complexity theory in health and social care: a scoping review protocol. Issue 7 (28th July 2021) - Carroll, Aine; Stokes, Diarmuid; Darley, Andrew
Abstract : Introduction: Despite the use of a wide variety of improvement tools and approaches, healthcare organisations continue to struggle in several key areas. Complexity-informed approaches have the potential to offer health and social care a new paradigm for understanding, designing, implementing and evaluating solutions, yet so far has failed to gain the traction anticipated some years ago. There is a growing need for high quality syntheses of the existing knowledge base in this area and given the diversity of theory and approaches, a scoping review is the best approach to curate this knowledge. Methods: A scoping review of relevant literature from January 2000 to present, using the refined Arksey and O'Malley six-stage framework will be conducted. This protocol will follow the Preferred Reporting Items for Systematic Reviews and Meta-analysis Protocols Extension for Scoping Reviews. A three-step search strategy will be used. An initial search of databases will be undertaken to identify key search terms followed by an analysis of retrieved papers title and abstract text words, and of index terms used to describe the articles. A second search using all identified keywords and index terms will then be undertaken across all included databases. Third, the reference lists of identified reports and articles will be searched. Authors of primary articles will be contacted and a search for grey material performed. Finally, a complete search strategy of one major database will be included. Ethics and dissemination: As this is a scoping review, ethical approval is not required. The results of the scoping review will be published in a peer-reviewed journal and presented at national and international conferences and will guide a large research project investigating teamwork. All data will be stored in accordance with best General Data Protection Regulation practice. Registration: This scoping review protocol has been registered with Open Science Framework.